2019
DOI: 10.1038/s41467-019-09478-2
|View full text |Cite
|
Sign up to set email alerts
|

Strong neuron-to-body coupling implies weak neuron-to-neuron coupling in motor cortex

Abstract: Cortical neurons can be strongly or weakly coupled to the network in which they are embedded, firing in sync with the majority or firing independently. Both these scenarios have potential computational advantages in motor cortex. Commands to the body might be more robustly conveyed by a strongly coupled population, whereas a motor code with greater information capacity could be implemented by neurons that fire more independently. Which of these scenarios prevails? Here we measure neuron-to-body coupling and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 47 publications
6
20
0
Order By: Relevance
“…c Phase histograms of two medial septal rhythmic neurons simultaneously recorded during theta (top) and stepping (bottom) cycles (data are duplicated to illustrate rhythmicity) that separate populations of medial septal cells specialized to coordinate theta rhythmic population activity and stepping related locomotor activity in the navigation system. This can be interpreted in concert with a recent observation in motor cortical neurons, where strong neuron to population coupling implied weak neuron to body-movement coupling (Kells et al 2019). From an evolutionary perspective, body movement variables may provide temporal windows for synchronizing neural computations in body-relevant timescales, crucial for behavior.…”
Section: Discussionsupporting
confidence: 67%
“…c Phase histograms of two medial septal rhythmic neurons simultaneously recorded during theta (top) and stepping (bottom) cycles (data are duplicated to illustrate rhythmicity) that separate populations of medial septal cells specialized to coordinate theta rhythmic population activity and stepping related locomotor activity in the navigation system. This can be interpreted in concert with a recent observation in motor cortical neurons, where strong neuron to population coupling implied weak neuron to body-movement coupling (Kells et al 2019). From an evolutionary perspective, body movement variables may provide temporal windows for synchronizing neural computations in body-relevant timescales, crucial for behavior.…”
Section: Discussionsupporting
confidence: 67%
“…Similarly, application of muscimol resulted in a large increase in synchrony for both normal and RTT rats. This result is somewhat surprising considering that stronger inhibition is often associated with reduced synchrony in theory 13,33 and GABA agonists can result in reduced synchrony 14 , but our finding is consistent with a recent study that applied muscimol in motor cortex of awake rats 7 .…”
Section: Resultssupporting
confidence: 91%
“…Precisely how much and what kind of synchrony is best for motor coding and how motor function depends on changes in synchrony is poorly understood. Previous studies have shown that significant synchrony and correlations exist among neurons in motor cortex [4][5][6][7] . Is this coordinated activity beneficial or is it actually limiting the motor code?…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations